(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article provides important information on physical education and culture, their basic concepts, as well as the tools of physical culture, a general description of physical qualities in physical education, and methods for monitoring their development.